Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 6 - Section 6.3 - Equations with Parentheses - Exercises: 51

Answer

x=6

Work Step by Step

Simplifying 5x + -10(3x + -6) = 3(24 + -9x) Reorder the terms: 5x + -10(-6 + 3x) = 3(24 + -9x) 5x + (-6 * -10 + 3x * -10) = 3(24 + -9x) 5x + (60 + -30x) = 3(24 + -9x) Reorder the terms: 60 + 5x + -30x = 3(24 + -9x) Combine like terms: 5x + -30x = -25x 60 + -25x = 3(24 + -9x) 60 + -25x = (24 * 3 + -9x * 3) 60 + -25x = (72 + -27x) Solving 60 + -25x = 72 + -27x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '27x' to each side of the equation. 60 + -25x + 27x = 72 + -27x + 27x Combine like terms: -25x + 27x = 2x 60 + 2x = 72 + -27x + 27x Combine like terms: -27x + 27x = 0 60 + 2x = 72 + 0 60 + 2x = 72 Add '-60' to each side of the equation. 60 + -60 + 2x = 72 + -60 Combine like terms: 60 + -60 = 0 0 + 2x = 72 + -60 2x = 72 + -60 Combine like terms: 72 + -60 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.